1996
DOI: 10.1083/jcb.135.5.1239
|View full text |Cite
|
Sign up to set email alerts
|

A major transmembrane protein of Golgi-derived COPI-coated vesicles involved in coatomer binding.

Abstract: Abstract. Formation of non-clathrin-coated vesicles requires the recruitment of several cytosolic factors to the Golgi membrane. To identify membrane proteins involved in this budding process, a highly abundant type I transmembrane protein (p23) was isolated from mammalian Golgi-derived COPI-coated vesicles, and its cDNA was cloned and sequenced. It belongs to the p24 family of proteins involved in the budding of transport vesicles (Stamnes, M.A., M.W. Craighead, M.H. Hoe, N. Lampen, S. Geromanos, P. Tempst, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
351
4
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(373 citation statements)
references
References 59 publications
14
351
4
4
Order By: Relevance
“…The absence of Arf proteins in the purified vesicles may be surprising in light of earlier data showing suprastoichiometric levels of Arfs over COPI subunits when vesicles were produced in vitro in the presence of guanosine 5Ј-O-(3-thio)triphosphate (GTP␥S) (Serafini et al, 1991;Rothman, 1994;Sohn et al, 1996). However, it later became evident that Arf GTPase activation proteins play essential roles in vesicle biogenesis and specificity of cargo selection (Goldberg, 1998;Lee et al, 2005), making GTP hydrolysis and dissociation of Arfs from the nascent bud or vesicle likely.…”
Section: Discussionmentioning
confidence: 95%
“…The absence of Arf proteins in the purified vesicles may be surprising in light of earlier data showing suprastoichiometric levels of Arfs over COPI subunits when vesicles were produced in vitro in the presence of guanosine 5Ј-O-(3-thio)triphosphate (GTP␥S) (Serafini et al, 1991;Rothman, 1994;Sohn et al, 1996). However, it later became evident that Arf GTPase activation proteins play essential roles in vesicle biogenesis and specificity of cargo selection (Goldberg, 1998;Lee et al, 2005), making GTP hydrolysis and dissociation of Arfs from the nascent bud or vesicle likely.…”
Section: Discussionmentioning
confidence: 95%
“…To achieve their correct targeting within the early secretory pathway they are in a dynamic equilibrium to form homo-and heterodimers with each other Jenne et al, 2002). All p24 family members are type I membrane proteins and share a common structure, with a short cytoplasmic tail containing binding signals for COP I and COP II coat complexes and a luminal domain with potential secretory cargo binding capabilities Sohn et al, 1996;Dominguez et al, 1998;Muniz et al, 2000). Proteomics analysis revealed that p24 family members are major constituents of COP I-coated vesicles (Stamnes et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In a yeast strain defective for vesicle fusion, a p24 knockout reduced the number of COPI-coated vesicles (Stamnes et al 1995). These data suggested that type I transmembrane proteins represent membrane receptors for coatomer and are actively required for the formation of COPI vesicles (Stamnes et al 1995;Sohn et al 1996). Surprisingly, however, in yeast the deletion of all p24 proteins showed only a reduction in the rate of transport of some cargo proteins (Springer et al 2000).…”
Section: Coat Recruitmentmentioning
confidence: 68%
“…2). Binding of coatomer to these signals depends more strongly on the phenylalanine than on the dilysine residues (Fiedler et al 1996b;Sohn et al 1996). These machinery signatures are recognized exclusively by g-COP (Bethune et al 2006).…”
Section: Coat Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation